PENDEKATAN PARTISIPATIF DALAM PEMBANGUNAN INFRASTRUKTUR DI KECAMATAN CIAWI - goo, frans; Hernawan, Denny; Goris Seran, Gotfridus (Universitas Djuanda, 2019)
This study aims to analyze the implementation of infrastructure development programs and map out what factors influence infrastructure development programs. This research took place in Ciawi Sub-District, Bogor Regency, West Java Province, Indonesia. The research method used a descriptive analysis method with a qualitative approach. The determination of informants was carried out by purposive sampling, namely people who knew the infrastructure development program in Ciawi District. Data collection used observation and in-depth interviews. Data analysis used qualitative descriptive analysis. The results of this study indicate that the implementation of Participatory Development in Ciawi Sub-District, Bogor Regency, West Java Province, has been implemented well, as indicated by the community's participation in the development planning and implementation of infrastructure development. Support factors that influence participatory infrastructure development are community awareness, community participation, and local governments, while the inhibiting factors for participatory infrastructure development are the quality of public education, the level of community income, and development facilities/equipment.